2012
DOI: 10.1128/mcb.00551-12
|View full text |Cite
|
Sign up to set email alerts
|

Functions and Regulation of Circular Dorsal Ruffles

Abstract: bCells construct a number of plasma membrane structures to meet a range of physiological demands. Driven by juxtamembrane actin machinery, these actin-based membrane protrusions are essential for the operation and maintenance of cellular life. They are required for diverse cellular functions, such as directed cell motility, cell spreading, adhesion, and substrate/matrix degradation. Circular dorsal ruffles (CDRs) are one class of such structures characterized as F-actin-rich membrane projections on the apical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
143
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(156 citation statements)
references
References 111 publications
(208 reference statements)
11
143
2
Order By: Relevance
“…Hence, the loss of membrane ruffling, and in particular dorsal ruffling, would appear to fully account for the reduced macropinocytic activity as measured by fluid-phase uptake assays. The contribution of dorsal ruffling to macropinocytosis has been a subject of some debate (Buccione et al, 2004;Hoon et al, 2012;Suetsugu et al, 2003). Although SNX5 is found on macropinosomes derived from peripheral and dorsal ruffles, our findings indicate that SNX5 is essential only for dorsal-rufflederived macropinosomes.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Hence, the loss of membrane ruffling, and in particular dorsal ruffling, would appear to fully account for the reduced macropinocytic activity as measured by fluid-phase uptake assays. The contribution of dorsal ruffling to macropinocytosis has been a subject of some debate (Buccione et al, 2004;Hoon et al, 2012;Suetsugu et al, 2003). Although SNX5 is found on macropinosomes derived from peripheral and dorsal ruffles, our findings indicate that SNX5 is essential only for dorsal-rufflederived macropinosomes.…”
Section: Discussioncontrasting
confidence: 42%
“…This study, which has identified SNX5 as a regulatory component of macropinocytosis derived from dorsal ruffles, will therefore provide a targeted approach to determine the effect of inhibiting one major pathway of macropinocytosis in vivo. In addition, and more broadly, the functions of dorsal ruffling, which have remained elusive (Hoon et al, 2012), will also be able to be directly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) rapidly redistribute to CDRs upon PDGF stimulation and that this redistribution is linked to focal adhesion turnover and cell migration (Gu et al, 2011;Hoon et al, 2012). We first addressed whether MICAL-L1 KD in human fibroblasts affected focal adhesions at steady state.…”
Section: Mical-l1 Is Required For Pdgf-induced Focal Adhesion Turnovermentioning
confidence: 99%
“…During this process, extracellular growth factors activate receptor tyrosine kinase (RTK)-dependent signaling, leading to extensive actin cytoskeleton remodeling and to the formation of unique specialized structures, such as circular dorsal ruffles (CDRs), lamellipodia and filopodia. CDRs are highly dynamic ring-shaped structures that are rich in filamentous actin (F-actin), and form on the dorsal surface of epithelial cells and fibroblasts in response to stimulation with growth factors, such as platelet-derived growth factor (PDGF) and epidermal growth factor (EGF) (Hoon et al, 2012). Moreover, CDRs have been implicated in macropinocytosis (Dowrick et al, 1993), recycling of integrins (Gu et al, 2011), rapid actin cytoskeleton remodeling during cell migration (Buccione et al, 2004), and in the internalization and sequestration of a number of RTKs, leading to their downregulation (Orth and McNiven, 2006).…”
Section: Introductionmentioning
confidence: 99%